Transfer of Content Development Across Practica in Physical Education Teacher Education - DERVENT, FATİH (HUMAN KINETICS PUBL INC, 2018)
Purpose: Instructional tasks are a form of content knowledge that can be defined as specialized content knowledge (SCK). We examined the changes in the use of instructional tasks and SCK index scores of preservice teachers from methods to final practicum. Method: Five preservice teachers were observed through the methods practicum where they taught a small group consisting of six to eight students and then through final practicum where they taught whole intact classes. A modified version of content development categories and formula to measure the depth of content development was used. SCK index scores of the preservice teachers created by the formula were used to compare the changes from methods with final practicum. Results: The results showed an increase in the mean SCK index scores of the preservice teachers from methods practicum to final practicum. The use of informing and extending-applying tasks decreased in the final practicum, while an increase occurred in the use of refining and applying tasks. Discussion/Conclusion: Increase in the mean SCK index scores seemed to reflect the strong SCK emphasis of the physical education teacher education program. It can be concluded that SCK can and should be taught to preservice teachers.
Keywords: content knowledge; specialized content knowledge; PEDAGOGICAL CONTENT KNOWLEDGE; ACCOUNTABILITY; CONCEPTIONS